Religious Ambivalence, Liminality, and the Increase of No Religious Preference in the United States, 2006-2014 - Hout, Michael (Journal for the scientific study of religion, 2017)
Americans identified less and less with organized religion over the past two decades. Yet apparently, many people who no longer identify with a religion are not consistently nonreligious. Reinterviews reveal that many people who express no religious preference in one survey name a religion when asked the same question in a subsequent interview. Past research called this phenomenon a liminal status. This article improves estimates of liminality by using three interviews and a better statistical model. About 20 percent of Americans were liminal in recent years, 10 percent were consistently nonreligious, and 70 percent were consistently religious. Falling religious identification in cross-sectional data over the last three decades reflects slow change in religious identity, but some of the rise of the nones is due to more liminals saying they have no religion. Liminals appear equally among people raised conservative Protestant, mainline Protestant, or Catholic.